Asians—a Doping-Friendly Race? Antidoping Research and Popular Discourse on Race in the Postgenomic Era. Issue 1 (1st March 2016) - Hyun, Jaehwan
Abstract : There has been a growing concern about a new way of thinking about race in genomics. STS scholars have tried to make sense of the ways race came to be a part of the scientific, medical, and legal fields in the name of genomics. This article adds to this STS literature on race and genomics with an analysis of antidoping science, a circuit of knowledge making that reifies race in terms of genomics but that thus far has been ignored by STS scholars. By engaging with the STS perspective on genomics and race, in this article I examine how antidoping regulatory knowledge on doping markers travels and how its operations are carried out both inside and outside this regulatory science. This study traces knowledge making about steroid doping regulations and its journey through the media and cyberspace, thus showing that regulatory efforts against doping were incidentally linked to the shaping of the idea of race in relation to genomics and personalized medicine, and especially that of Asian race. While the regulations, recommendations, and debates on the use of race in terms of genomics focused on biomedical research and practice, antidoping scientists are regulatory scientists on the periphery of biomedicine. Antidoping scientists did not, then, engage with debates on the use of racial categories when applying concepts of personalized medicine and pharmacogenomic studies in biomedicine. They used racial categories in their studies of the UGT2B17 gene without concern, and their research reinforced the shaping of racialist discourses on the idea of Asians as a doping-friendly race in the media and cyberspace. This case study suggests that, to improve academic and political intervention on race and genomics, STS scholars should expand their studies into peripheral disciplines of biomedicine such as antidoping science and other human regulatory sciences.